Marketing Communication Strategy for MSMEs Through Content Short Video 2022–2025: Literature Review - Ni Made Intan Dwi Sukma; Wayan Indra Surya Pratiwi; Ni Komang Pasek Riski Artaningsih; Ni Luh Wina Antari; I Nyoman Surpa Adisastra (International Journal of Social Studies, 2026)
The rapid development of the new media ecosystem has fundamentally transformed the landscape of digital interaction, demanding Micro, Small, and Medium Enterprises (MSMEs) to adopt short video-based marketing communication strategies. This research aims to analyze determinant factors, effective strategies, and implementation challenges through a literature study of 20 scientific articles (2022–2025) using the TCCM (Theory, Context, Characteristics, Method) analysis framework. The synthesis results show that short video adoption is driven by the adaptation of audience preferences in the new media era, the efficiency of organic reach costs due to content distribution accessibility, and mediatization pressure in the form of competitive pressure. The most effective communication strategies integrate edutainment based soft-selling approaches, visual hook optimization within the AIDA framework, and the utilization of interactive features to trigger consumer participation. However, the implementation of these strategies is still hindered by digital literacy gaps, content inconsistency, and ROI measurement ambiguity due to dependence on third-party platforms. This research concludes the need for developing adaptive mentoring models and independent performance evaluation metrics to ensure the sustainability of MSME competitiveness in the digital ecosystem.